The Impact of Indian Food Inflation on Food Security in Bangladesh 2022 - Ulhaq, Daffa Dhiya; Amalia, Novi Rizka (Jisiera: The Journal of Islamic Studies and International Relations, 2024)
Food inflation in India, caused by climate change, heat waves, and droughts, has significantly impacted Bangladesh's food security. This study examines the impact of India's food inflation on Bangladesh, using food security and food inflation theories. The findings reveal that rising food prices in India directly affect Bangladesh's food import prices, threatening its welfare and health. To improve food security, Bangladesh should diversify food sources, strengthen distribution systems, and support sustainable food production. Regional and international cooperation is crucial to address the impact of food inflation on Bangladesh's food security. The study concludes that effective policies and cooperation between countries are essential for addressing this issue.